Pisonia Grandis R.Br – A Medicinal Plant: A Review - A. ELUMALAI; M. CHINNA ESWARAIAH; HABIBUR RAHMAN (International Journal of Pharma and Bio Sciences, 2012)
Pisonia grandis R.Br (Nyctaginaceae) is widely distributed throughout India and is a widespread evergreen tree commonly known as ‘Leechai kottai keerai’. Leaves, stems and roots of this species are extensively used by the tribals in the preparation of several folk medicines. The plant is traditionally used as anti-rheumatic and anti-fungal. This plant is also pharmacologically studied for its anti-fungal, anti-oxidant, anti-microbial, anti-inflammatory, anti-diabetic, diuretic, analgesic and wound healing properties. Further studies reveal the presence of various phytochemical constituents mainly alkaloids, phenolic compounds and flavanoids. This will be helpful to create interest towards Pisonia grandis and may be useful in developing new formulations with more therapeutic and economical value.